Influence of Juvenile Hormone and its Receptors on the Immune system during Metamorphosis of Drosophila melanogaster - Fettinger, Verena (Jihočeská univerzita, 2020)
Juvenile hormone is known to have both immune suppressing and developmental effects in several insect species. During Drosophila melanogaster metamorphosis, several events require regulation by JH which is mediated through the JH receptors Methoprene-tolerant (Met) and germ cell expressed (Gce). This thesis is focused on the effect JH and its receptors have during metamorphosis and whether they can be related to an occurring immune challenge or developmental events.
Influence of Juvenile Hormone and its Receptors on the Immune system during Metamorphosis of Drosophila melanogaster
Keywords: Drosophila melanogaster; Juvenile Hormone; JH receptors; immune system; AMP expression; Mutations; metamorphosis; timepoints; immune regulation; development; Drosophila melanogaster; Juvenile Hormone; JH receptors; immune system; AMP expression; Mutations; metamorphosis; timepoints; immune regulation; development